PERTANGGUNGJAWABAN TINDAK PIDANA PENGEDAR GANJA YANG DILAKUKAN OLEH ANAK (BERDASARKAN PUTUSAN No. 10/PID.SUS.ANAK/2015/PN.STB - Bella Khairunnisa; Joni Firdaus Ginting; Rini Damayanti Sijabat; Rahmayanti Rahmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Government policy in providing protection to children, especially in the crime of cannabis dealers becomes very important. Because children are the next generation to continue the nation's development. There are 2 factors that cause this crime, namely external factors (free will, curiosity) and internal factors (economic conditions and the surrounding environment). Regulations regarding this criminal act are regulated in article 6 Number 35 of 2009 concerning narcotics, governing criminal offenses, regarding specific criminal sanctions as well as the types of sanctions and the length of the crime. In this case, the judge's policy should not be based too much on Law Number 11 of 2012 concerning the juvenile justice system, which continues to interpret the existing law. And the government should provide the assistance of a supervisory body, namely the Special Child Development Institute. and create educational and coaching programs that are supervised by the Penitentiary.